THE EFFECTIVENESS OF E-COMMERCE PLATFORMS IN ENHANCING THE MARKETING OF MSME PRODUCTS IN SEDENGANMIJEN VILLAGE, SIDOARJO REGENCY - Hernandya, Clarafika Dian; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate how effective e-commerce is in enhancing the performance of Micro, Small, and Medium Enterprises (MSMEs) in Sedenganmijen Village, specifically focusing on Dapur Geliz as a case example. Method: The research employs a qualitative descriptive method, utilizing interviews, observations, and document analysis to gather deeper insights. Result: The research findings reveal that the implementation of e-commerce has a positive influence on three primary indicators: resource efficiency, activity outcomes, and alignment with the strategic plan. E-commerce aids in lowering operational costs, optimizing raw material use, and speeding up production processes. There has been an increase in sales, customer loyalty, and favorable consumer reviews, indicating significant improvement in business results, while digital strategies align with MSMEs’ initial goals to broaden market reach and elevate customer satisfaction. Novelty: These findings demonstrate that the utilization of e-commerce serves as a strategic tool for enhancing competitiveness and ensuring the sustainability of MSMEs, particularly in rural areas adapting to advancements in digital technology, and provide empirical evidence supporting the integration of resource efficiency management theory into digital business practices.